Role of Imaging in Left Atrial Appendage Occlusion - Mathieu Lempereur; Adel Aminian; Raluca Dulgheru; Tom De Potter; Cécile Oury; Patrizio Lancellotti (International Journal of Cardiovascular Practice, 2017)
Percutaneous left atrial appendage (LAA) occlusion is now a valid alternative to long-term oral anticoagulation in patients with non-valvular atrial fibrillation at high thrombo-embolism risk, especially for patients who are considered ineligible for anticoagulation. The most frequently used occluders worldwide include the WATCHAMN (Boston Scientific, Natick, MA, USA) and the Amplatzer Cardiac Plug or Amulet (St. Jude Medical/Abbott, St Paul, MN, USA) devices. Multimodality imaging is key in the understanding of 3D aspects of the LAA and surrounding structures anatomy. Imaging is essential for procedural planning, during each step of the procedure and for device surveillance after implantation. Multimodality imaging, including 2D/3D echocardiography, fluoroscopy, and cardiac computed tomography can increase the safety and efficacy of the procedure.